Analisis Kinerja Keuangan Bank BUMN dan Bank Swasta Indonesia: Studi Komparatif - Willa Fatika Sari; Darman Saputra; Yasmin Yasmin (Penerbit Goodwood, 2024)
Purpose: This study assesses and compares the financial performance of state-owned and private banks in Indonesia from 2019 to 2021. This study focuses on evaluating key financial indicators to monitor the financial structure and efficiency of banking institutions continuously amid increasing competition in the banking sector.Methodology: This study utilizes several financial ratios and applies independent sample t-tests to analyze the financial performance of state-owned and private banks. The key ratios analyzed include (Equity to Total Assets Ratio), ECTAR (Equity to Customer Assets Ratio), IMAEAR (interest margin to average earnings assets ratio), LLCR (Loan Loss Coverage Ratio), DTCR (Debt to Capital Ratio), LDR (Loan to Deposit Ratio), and CAR (Capital Adequacy Ratio).Results: State-owned banks are financially weaker than private banks. Furthermore, there is no significant difference in the average financial performance of state-owned and private banks when measured using EATAR and ECTAR ratios. However, clear differences are observed between these two banking groups in terms of the IMAEAR, LLCR, DTCR, LDR, and CAR ratios.Conclusions: Financial performance in Private Banks is superior relative to State-Owned Banks. This is because Private Banks have better capital management, higher loss reduction, more equity owned by the company compared to debtholders, a large amount of credit disbursed, and based on CAR are more able to accommodate possible losses.Limitations: This study analyzes financial performance from 2019 to 2021, which may not reflect long-term trends or the effects of external factors like global crises or regulatory changes. It also focuses on a limited set of financial ratios.Contribution: This study compares the financial performance of state-owned and private Indonesian banks, offering insights for banks, regulators, and investors on performance differences and areas for improvement in state-owned banks.